Teatr i muzyka dla najnajmłodszych. Doświadczenia poznańskie w badaniach własnych - Wieczorek, Maria (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2021)
When should we start introducing children into the world of culture? For the past few years the boundary has been shifting and now it applies to the youngestest, in the first months of their lives. For them both performances and concerts are organized. In this article I describe the role theatre and music play in the development of the youngest, the origins of theatre and first musical forms for children; I also discuss the institutions in Poznań which organize events for babies.
Theater and music for the youngestest – Poznań experience in the author’s own research
Keywords: teatr; muzyka; małe dziecko; theatre; music; baby; child